2019
DOI: 10.1002/adhm.201900408
|View full text |Cite
|
Sign up to set email alerts
|

The Prospects for Biodegradable Zinc in Wound Closure Applications

Abstract: Zinc is identified as a promising biodegradable metal along with magnesium and iron. In the last five years, considerable progress has been made on understanding the mechanical properties, biodegradability, and biocompatibility of zinc and its alloys. A majority of these studies focused on using zinc for absorbable cardiovascular and orthopedic device applications. However, it is likely that zinc is also suitable for other biomedical applications.In this work, the prospects for zinc in the fabrication of wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 116 publications
0
36
0
Order By: Relevance
“…The in vitro corrosion behavior of pure Zn in different corrosive mediums has been extensively investigated by researchers [ 85 , 256 , [267] , [268] , [269] ]. For example, the corrosion behavior of pure Zn in two corrosive solutions, PBS and RSS, and two natural body fluids, human plasma and whole blood, was first reported by Torne et al [ 256 ] and their results indicated that corrosion rates decreased with immersion time for plasma and whole blood, while they increased during immersion in PBS and RSS.…”
Section: Corrosion Mechanisms and Degradation Behaviors Of Pure Zn Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro corrosion behavior of pure Zn in different corrosive mediums has been extensively investigated by researchers [ 85 , 256 , [267] , [268] , [269] ]. For example, the corrosion behavior of pure Zn in two corrosive solutions, PBS and RSS, and two natural body fluids, human plasma and whole blood, was first reported by Torne et al [ 256 ] and their results indicated that corrosion rates decreased with immersion time for plasma and whole blood, while they increased during immersion in PBS and RSS.…”
Section: Corrosion Mechanisms and Degradation Behaviors Of Pure Zn Anmentioning
confidence: 99%
“…Fig. 1 shows an illustration of various in vivo studies using Zn-based materials for potential clinical applications [ [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…However, its application was limited because of the significant toxicity [ 22 ]. Therefore, the sustained and controlled release of zinc ions have attracted considerable attentions [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, their corrosion rate is too high for many applications. Moreover, the corrosion process is accompanied by hydrogen production, which may have a detrimental effect on the healing process [15,16]. Due to that side effect, iron-and zinc-based materials have been suggested as alternative potential metallic absorbable implants for both cardiovascular and bone implants [15][16][17].…”
Section: Introductionmentioning
confidence: 99%